Andrographolide attenuates bupivacaine-induced cytotoxicity in SH-SY5Y cells through preserving Akt/mTOR activity - Zhang H; Wang W; Du Q (Dove Medical Press, 2019)
Huiyuan Zhang,1 Weiwei Wang,1 Qian Du21Department of Neurology, Liaocheng People’s Hospital, Liaocheng, Shandong, 252000, People’s Republic of China; 2EEG Room, Liaocheng People’s Hospital, Liaocheng, Shandong 252000, People’s Republic of ChinaBackground: Bupivacaine (Bup) is the most commonly used local anesthetic. However, Bup induces cytotoxicity, especially in older patients. Recent reports have indicated that andrographolide (Andro) exhibits protective effects on human neurons. Nevertheless, whether Andro can inhibit Bup-induced cytotoxicity remains unclear. As such, we investigated the effect of Andro on Bup-induced cytotoxicity of SH-SY5Y cells in the present study.Methods: Western blotting was used to examine expression of Bax, Bcl2, active caspase 3, p-Akt, and p-mTOR in SH-SY5Y cells. In addition, ELISA was used to detect levels of total glutathione and reactive oxygen species in cells.Results: We found that Andro attenuated Bup-induced cytotoxicity of SH-SY5Y cells. In addition, Andro inhibited Bup-induced apoptosis via downregulating the expression of Bax and active caspase 3 and upregulating the proteins Bcl2, p-Akt, and p-mTOR in SH-SY5Y cells. Moreover, Andro alleviated Bup-induced oxidative damage in SH-SY5Y cells via downregulating the level of reactive oxygen species and upregulating of the level of total glutathione. More significantly, inhibition of Akt abolished the protective effect of Andro in Bup-treated SH-SY5Y cells.Conclusion: Our findings indicated that Andro played a neuroprotective role via preserving Akt/mTOR activity and increasing antioxidative status in Bup-treated SH-SY5Y cells. Therefore, Andro may be a potential agent for the treatment of human cytotoxicity induced by Bup.Keywords: andrographolide, bupivacaine, apoptosis, Akt, cytotoxicity